Educational Efforts to Improve Public Awareness about Greening and Healthy Lifestyle in Urban Areas - Shereen Aprillia; Jolene Budiono; Meiliyana Wijaya (Institute for Research and Community Services, 2022)
Public awareness and concern about greening and healthy lifestyles in preserving the environment and improving health status are crucial despite the covid-19 pandemic. One approach to deal with this issue is by spreading the information and taking promotive actions which aim to increase public awareness of the importance of greening and healthy lifestyles in their daily lives. Various online educational activities for communities are needed to increase their knowledge and concern. In this regard, the Daerah Binaan (DABIN) unit and the Hazard Analysis and Critical Control Point (HACCP) of the Faculty of Medicine and Health Sciences at Atma Jaya Catholic University of Indonesia held a SEHATI challenge and an educational seminar